Isolation of methicillin-resistant staphylococcus aureus (mrsa) from pork meat in kota bharu, kelantan - Lak Ong’a A/P Udom (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT55204 - Research Project. Foodborne disease, often known as food poisoning, refers to any ailment induced by ingesting contaminated food containing hazardous bacteria, such as Staphylococcus aureus from pork meat. The condition could have been worse if the bacteria was antimicrobial-resistant, such as Methicillin-Resistant Staphylococcus aureus (MRSA), which is regularly found in pigs. This study aims to evaluate whether MRSA is present in pork meat in Kota Bharu, Kelantan. Thus, 30 samples of fresh pork meat were gathered from the Kota Bharu market, bacteria were isolated and identified, and an antibiotic sensitivity test (AST) using the Kirby-Bauer disk method was conducted. The obtained data were analyzed by manual data analysis. The results showed that 21 of 30 (70%) pork meat samples from the market were colonized with S. aureus, and 60% of them tested positive for MRSA. The outcome shows that MRSA in pork meat can be spread to humans through meat handling and potentially cause food poisoning. Keywords: Foodborne disease, antimicrobial-resistant, Staphylococcus aureus, MethicillinResistant Staphylococcus aureus (MRSA), pork meat